Effects of Postpartum Stressors on Parenting Behaviors - Derya Kaya Şenol; Edanur Tar Bolacalı; Cansu Ağralı (Ebelik ve Sağlık Bilimleri Dergisi, 2025)
Objective: This study was conducted to determine the effects of postpartum stressors on parenting behaviors.Methods: The population of this descriptive-relational study consisted of 520 postpartum women who gave birth in a hospital in southern Türkiye. The data were collected face-to-face between January and December 2022. The data of the study were collected face to face between January and December 2022 using the “Personal Information Form”, “Postpartum Stress Scale” and “Postpartum Parental Behavior Scale”.Results: Number of children, employment status, dependency status, spouse's age, spouse's occupation, place of residence, social security status, pregnancy planning status, and education on pregnancy and childbirth were determined as significant predictors of postpartum stress; any problems during childbirth were determined as significant predictors of postpartum parenting behaviors (p